Neighbourhood Watch in a Digital Age Between Crime Control and Culture of Control - Lub, Vasco (Crime Prevention and Security Management, 2018)
Drawing on data from 340 municipalities in the Netherlands as well as ethnographic fieldwork, this book presents original research on neighbourhood watch groups to illustrate how their actions contribute to collective efficacy and lower crime levels. Technological developments like social media and smartphones have changed the landscape of coproduction in public safety, and this book addresses the resultant issues involved with creating effective policy. While digital innovations and securitization have made neighbourhood watch groups effective, they have simultaneously increased the risk of vigilantism, and Lub reveals how stigmatization, ethnic profiling and excessive social control are very real issues, especially in suburban middle-class districts. Crucially, this study raises questions about how the increasing popularity of community crime prevention in a digital age should be framed: as a welcome civic contribution to crime control, or as a social phenomenon adding to an undesirable culture of control. Criminologists, city officials, policy makers and anyone studying neighbourhood activism will find this a fascinating work on crime control. .